Impact of a front-of-pack nutritional traffic-light label on the nutritional quality and the hedonic value of mid-afternoon snacks chosen by mother-child dyads. (1st December 2019) - Poquet, Delphine; Ginon, Emilie; Goubel, Baptiste; Chabanet, Claire; Marette, Stéphan; Issanchou, Sylvie; Monnery-Patris, Sandrine
Abstract: The aim of this study was to assess the impact of a nutritional traffic-light label, the Nutri-Score, on snack choices in mother-child dyads and to assess a potential hedonic cost associated with a change in favour of healthier choices. French mothers and children (n = 95; children's age: 7–11 years) who participated were asked to choose, for themselves and for the other dyad member, a snack composed of one beverage and two food items selected among several products with different nutritional quality. In the first step, the products were presented without any information. In the second step, the products were labelled with the Nutri-Score. Mothers and children were asked to rate their liking for all proposed products before being informed of their nutritional quality. The nutritional quality, the hedonic score, and the estimated budget of the selected snacks were compared before and after labelling. As hypothesized, the Nutri-Score label led to a significant increase in the nutritional quality of the chosen snacks. The budget for the chosen snacks was unchanged or decreased after the nutritional labelling was applied. Children and mothers had significantly lower liking for the snacks after nutritional labelling than before nutritional labelling, suggesting a hedonic cost associated with a change in favour of healthier snack choices. This raises the question of the sustainability of the behavioural change induced by the Nutri-Score label.